Comparison of the Clinical Outcomes of Full‐Endoscopic Visualized Foraminoplasty and Discectomy Versus Microdiscectomy for Lumbar Disc Herniation. Issue 2 (16th December 2021) - Hua, Wenbin; Ke, Wencan; Wang, Bingjin; Xiang, Qian; Zhang, Yukun; Wu, Xinghuo; Li, Shuai; Wang, Kun; Zeng, Xianlin; Gao, Yong; Yang, Shuhua; Xiao, Baojun; et al.
Abstract : Objective: This retrospective case‐control study aimed to evaluate and compare the clinical outcomes of full‐endoscopic visualized foraminoplasty and discectomy (FEVFD) with microdiscectomy (MD) for lumbar disc herniation (LDH). Methods: Data from 198 patients who presented with LDH between January 2016 and December 2017 treated by either FEVFD or MD were retrospectively analyzed. The inclusion criteria were single‐level LDH, unilateral radiating leg pain with or without positive Lasegue's sign, and failure of standard conservative treatment for at least 12 weeks. The patients were categorized into an FEVFD group ( n  = 102) or an MD group ( n  = 96), according to the surgical procedure performed. Operative time, time in bed after surgery, postoperative hospitalization time, complications, and reoperations were recorded. Visual analog scales (VAS) for leg and back pain, Oswestry Disability index (ODI), 36‐Item Short‐Form Health Survey physical function (SF36‐PF), and bodily pain (SF36‐BP) scores were assessed and compared between the two groups. Results: The demographic data and baseline characteristics of the two groups were not significantly different. Operative time for the FEVFD group (73.82 ± 20.73 min) was longer than that for the MD group (64.74 ± 17.37 min) ( P  = 0.003), and fluoroscopy time for the FEVFD group (1.71 ± 0.58s) was longer than that for the MD group (1.30 ± 0.33s) ( P  < 0.001). However, time in bed experienced in the FEVFD group (8.51 ± 2.10 h) was less than that in the MD group (9.24 ± 2.01 h) ( P  = 0.014), and postoperative hospitalization time experienced in the FEVFD group (2.89 ± 0.83d) was also shorter than that in the MD group (4.94 ± 1.35d) ( P  < 0.001). All patients completed 24 months of follow‐up. Postoperative scores at each follow‐up for the VAS for leg and back pain, ODI, SF36‐PF, and SF36‐BP all improved significantly for both groups, as compared to the preoperative data ( P  < 0.05). The mean preoperative and postoperative scores for the VAS for leg and back pain, ODI, SF36‐PF, and SF36‐BP were not significantly different between the two groups. According to the modified MacNab criteria, the outcomes of the procedures were rated as excellent or good by 92.16% and 93.75% of the patients in the FEVFD and MD groups, respectively. One patient suffered a nerve root injury during the discectomy, one patient suffered from a dural tear, and two patients suffered from a residual herniation in the FEVFD group. One patient in the MD group suffered from poor wound healing. Moreover, recurrence happened in two cases in the FEVFD group, and in one case in the MD group. Conclusion: FEVFD and MD are both reliable techniques for the treatment of symptomatic LDH. FEVFD resulted in a more rapid recovery and equivalent clinical outcomes after 24 months of follow‐up. Abstract : Comparison of the Clinical Outcomes of Full‐Endoscopic Visualized Foraminoplasty and Discectomy Versus Microdiscectomy for Lumbar Disc Herniation.